al-Farhūd : the 1941 pogrom in Iraq - Moreh, Shmuel; Yehuda, Zvi; Vidal Sassoon International Center for the Study of Antisemitism (Universiṭah ha-ʻIvrit bi-Yerushalayim); Merkaz moreshet Yahadut Bavel (Or Yehudah, Israel) (Vidal Sassoon International Center for the Study of Antisemitism, 2010)
Introduction / Shmuel Moreh -- The pogrom (Farhūd) of 1941 in light of new sources / Zvi Yehuda -- National Socialism in the Arab Near East, 1933-1939 / Stefan Wild -- The sack of Baṣra and the Farhūd in Baghdad / Elie Kedourie -- The role of the Palestinian incitement and the attitude of Arab intellectuals to the Farhūd / Shmuel Moreh -- The anti-Jewish Farhūd in Baghdad, 1941 / Hayyim J. Cohen -- The Communists in Iraq and Rashīd ʻĀlī al-Kaylānī's revolt / Nissim Kazzaz -- The Baghdad pogrom and Zionist policy / Esther Meir-Glitzenstein -- The pogrom of June 1941 in the literature of Iraqi Jews in Israel / Shmuel Moreh -- List of victims of the Farhūd ; Map of the pogrom (Farhūd) ; Selected documents on the pogrom (Farhūd) / Zvi Yehuda